2005
DOI: 10.2151/jmsj.83a.45
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Atmospheric Aerosol at Aksu, an Asian Dust-Source Region of North-West China: A Summary of Observations over the Three Years from March 2001 to April 2004

Abstract: The observed maximum concentration of total suspended particles (TSP) was 5.2 mg m À3 during the dust event of April 2003. Variations in the TSP and PM 11 (particles smaller than 11 mm) show that high atmospheric concentrations were observed during dust events that occurred mainly in spring and summer. According to the meteorological observations, dust storms or blowing sand/dust occurred not only in spring, but also in summer and autumn, though floating dust occurred mainly in March and April. The frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Shifting the size fraction of dust particles is attributable to differences in settling velocity with size. For a dust event in March 2001, Mori et al (2003 reported aerodynamic mass size distributions sampled at Beijing, China, and at Yamaguchi, 1500 km downwind from Beijing, western Japan. Although the major peak of aerodynamic mass size distribution at Beijing was found at 4.7-7.0 µm, the peak in coarse mode at Yamaguchi was 3.3-4.7 µm.…”
Section: Deposition Of Giant Dust Particles and Transport Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shifting the size fraction of dust particles is attributable to differences in settling velocity with size. For a dust event in March 2001, Mori et al (2003 reported aerodynamic mass size distributions sampled at Beijing, China, and at Yamaguchi, 1500 km downwind from Beijing, western Japan. Although the major peak of aerodynamic mass size distribution at Beijing was found at 4.7-7.0 µm, the peak in coarse mode at Yamaguchi was 3.3-4.7 µm.…”
Section: Deposition Of Giant Dust Particles and Transport Processesmentioning
confidence: 99%
“…Continuous multi-year data of deposition flux have been reported for dusts transported from desert areas such as central and eastern Asia (Inoue and Naruse, 1987;Yabuki et al, 2005;Hsu et al, 2009;Sun et al, 2003;Ta et al, 2004;Zhang et al, 1993), North America (Reheis, 2006), and the Middle East and Sahara (Ganor et al, 2003;Offer and Goossens, 2004;Pye, 1992;Nihlén et al, 1995;Loye-Pilot and Martin, 1996). Data of shorter (nearly 1 yr or event basis) periods have been reported much more (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of the ADEC Experiment (Aeolian Dust Experiment on Climate impact; Mikami, et al, 2002), PM 11 concentrations have been measured in the northern part of the Taklamakan desert from 2001 to 2004, by weighting filters collected with an Andersen-like cascade impactor (Yabuki et al, 2005). In Aksu, North of the Tarim Basin, the minimum daily PM 11 concentration ranges between 54 and 70 µg m −3 .…”
Section: Daily Concentrationsmentioning
confidence: 99%
“…The Aksu Station is situated in an oasis, 80 km southeast of the Aksu city. The data of the routine meteorological observation, automated meteorological instruments and aerosol sampling in the experimental field were available (Yabuki et al 2005). The lidar observations were continuously conducted from April 11 to 21, 2002 except several power failures.…”
Section: Observation Sitementioning
confidence: 99%